Cytogenetic risk grouping by the monosomal karyotype classification is superior in predicting the outcome of acute myeloid leukemia undergoing allogeneic stem cell transplantation in complete remission. (21st November 2013) - Hemmati, Philipp G.; Schulze‐Luckow, Anthea; Terwey, Theis H.; le, Philipp; Vuong, Lam G.; Dörken, Bernd; Arnold, Renate
Abstract We retrospectively analyzed the impact of cytogenetic abnormalities grouped according to the monosomal karyotype (MK) classification or the Southwest Oncology/Eastern Cooperative Oncology Group (SWOG/ECOG) definition in 263 patients with acute myeloid leukemia (AML) who underwent allogeneic stem cell transplantation (alloSCT) in complete remission (CR) at our center. Risk grouping using the MK criteria shows a highly significant difference in 5‐yr overall survival (OS) ranging between 67%, for the most favorable, and 32%, for the poorest risk group (P = 0.001). Although similarly precise in predicting OS, the MK scheme better separates patients with respect to relapse incidence as compared to the SWOG/ECOG grouping (P = 0.0001 vs. P = 0.01). Notably, patients displaying non‐MK abnormalities (MK−) had a 5‐yr relapse incidence identical to those cytogenetically normal (CN), that is 24%. Multivariate analysis revealed that the MK classification is an independent prognosticator and superior in predicting OS (hazard ratios, HR 3.74, P = 0.01) and relapse incidence (HR 3.74, P = 0.005) as compared to the SWOG/ECOG criteria. Finally, subgroup analysis revealed that the prognostic capacity of the MK classification is highly significant in patients treated with standard myeloablative conditioning prior to alloSCT (P = 0.0011 for OS, P = 0.0007 for relapse). In contrast, the MK grouping failed to predict OS or relapse incidence in patients treated with reduced intensity conditioning. Taken together, these results indicate that the MK classification is superior in predicting the overall outcome of patients with AML undergoing alloSCT in CR. Furthermore, our data suggest that the genetic risk profile of MK− and CN patients is mostly overlapping in this setting.